The Welfare Implications of Services Liberalization in a Developing Country : Evidence from Tunisia - Jouini, Nizar; Rebei, Nooman (Washington, D.C. : International Monetary Fund, 2013)
We propose an integrated method based on a two-sector small open economy dynamic and stochastic general equilibrium model to estimate non-tariff barriers and quantify the impact of services liberalization. The major component of trade barriers is explicitly modeled through the introduction of entry-sunk costs. Hence, liberalization is treated assuming a government's policy decision aimed at reducing those costs. Then, we estimate the model using Bayesian techniques for Tunisia and the Euro Area. The paper presents a precise quantitative evaluation of services trade barriers as the difference between entry-sunk costs in Tunisia versus the Euro Area. We find significant welfare benefits in addition to aggregate and sectoral growth gains the Tunisian economy could attain following services liberalization. Surprisingly, the goods sector is the one that benefits the most from services liberalization in the short- and long-term horizons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet